Psychological And Technological Features of Increasing the Efficiency of Educational Activity of Talented Students in Presidential Schools. - Hojiyeva Zulfiya Oktamovna; Jalilova Dilshoda Ural Kizi (Zien Journals, 2022)
Presidents to improve the educational activities of gifted students, as well as to attract qualified psychologists to educational institutions and continue the educational activities of gifted students. consideration of privatization. In addition to theoretical information on the above issues, this article also provides technical recommendations for monitoring the educational activities of gifted students of Presidential Schools.
Keywords: Presidential schools; gifted students; educational activities; psychologists